Estudio paisajístico de los aspectos biofísicos y antrópicos en dos espacios urbanos de la ribera del río Rímac en Lima, Perú - Santiváñez López, Miguel Ángel (2024)
The objective of this paper is to describe and contrast the biophysical and anthropic aspects in two urban spaces adjacent to the Rímac River in the city of Lima: the Malecón de la Amistad, and the viewpoints of the old Reserved Zone project of the Rimac River. The approach is qualitative with a descriptive scope and the landscape analysis criteria of Castillo et al. (2014) to highlight the forms of use enabled by anthropic intervention in relation to the natural ecosystem. The results suggest that these spaces have been intervened to direct the movement of their visitors, but in both cases the material elements of the urban scene show a precarious integration between the biophysical and the anthropic, which reflects a contradictory interventionism that imposes and cancels various forms of use for visitors, exacerbating the spatial fragmentation.